Cardiogenic Stroke Despite Low CHA2DS2‐VASc Score: Assessing Stroke risk by Left Atrial Appendage Anatomy (ASK LAA). (17th August 2015) - NEDIOS, SOTIRIOS; KOUTALAS, EMMANUEL; KORNEJ, JELENA; ROLF, SASCHA; ARYA, ARASH; SOMMER, PHILIPP; HUSSER, DANIELA; HINDRICKS, GERHARD; BOLLMANN, ANDREAS
Assessing Stroke risK by LAA Anatomy (ASK LAA) Introduction In patients with atrial fibrillation (AF), LAA morphology has been suggested to modify thromboembolic event (TE) risk. We tested the hypothesis that TE in low‐risk patients is associated with LAA characteristics. Methods Of 2, 069 patients who underwent AF ablation, 25 (1.2%) had a prior TE and a low CHA2DS2‐VASc score (≤1). Those patients were matched for the CHA2DS2‐VASc criteria with 75 eventfree patients and CT data were compared. LAA measurements, morphology (Cactus, Chicken‐Wing, Windsock, Cauliflower), and takeoff of the superior and inferior edge in relation (higher or lower) to the respective takeoff of the adjacent pulmonary vein (PV) were determined. LAA flow in relation to heart rate was also compared. Results Univariate analysis showed that TE patients had a higher incidence of superior LAA takeoff (i.e., higher than the left superior PV; 28% vs. 4%, P = 0.002) and a higher incidence of hyperlipidemia (40% vs. 17%, P = 0.028), while LAA morphologies, inferior takeoff, and other LAA characteristics were similar between groups. Logistic regression revealed that a superior LAA takeoff (OR: 9.1, 95% CI: 2.1–38.6, P = 0.003) was the only independent predictor of TE. There was a negative correlation between heart rate and LAA flow (r = –0.2 cm/s pro bpm, P = 0.048), that was even more pronounced for the superior LAA takeoff (r = –0.67 cm/s pro bpm, P = 0.035). Conclusion A higher LAA takeoff is associated with a tachycardia‐mediated thrombogenic flow and an increased thromboembolic risk. These findings may have implications for anticoagulation management of AF patients with low CHA2DS2‐VASc scores and higher LAA takeoff.